SYNTHESIS AND ANTIBACTERIAL ACTIVITY OF CEPHALOSPORINS HAVING A CATECHOL IN THE C3 SIDE CHAIN - IIMURA, SEIJI; OKITA, TAKAAKI; KAMACHI, HAJIME; HASEGAWA, TOSHIFUMI; IMAE, KIYOTO; KAMEI, HIDEO; MASUYOSHI, SHINJI (Journal of antibiotics, 1993)
Cephalosporins having a catechol through a variety of linkages to the C3 position and a different C7 side chain were prepared. Among them, 3-(catechol-4-ylcarbonyloxy)methylcephalosporin (14) and 3-[(E)-3-(catechol-4-ylcarbonyloxy)-l-propen-l-yl]cephalosporin (10) showed excellent activity against Gram-negative activity including ceftazidime-resistant Escherichia coli, Pseudomonas aeruginosa, Xanthomonas maltophilia and Pseudomonas cepacia.